2005
DOI: 10.1002/jbm.b.30368
|View full text |Cite
|
Sign up to set email alerts
|

Novel silicon‐doped hydroxyapatite (Si‐HA) for biomedical coatings: An in vitro study using acellular simulated body fluid

Abstract: Magnetron co-sputtering was used to produce silicon-doped hydroxyapatite (Si-HA) as coatings intended for potential applications such as orthopedic and dental implants. It was found that the crystallinity of the as-sputtered coatings increased after annealing, resulting in a nanocrystalline apatite structure. Subsequently, the bioactivity of the coatings was evaluated in an acellular simulated body fluid (SBF). Physicochemical evaluation demonstrated that a carbonate-containing apatite layer, which is essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 41 publications
1
36
0
Order By: Relevance
“…59,60 In vitro studies have shown that these coatings exhibit enhanced bioactivity and biomineralisation over uncoated samples and pure HA coatings. [61][62][63] Fig. 3 shows a typical example of osteoblast response to a magnetron co-sputtered Si-HA thin film.…”
Section: Magnetron Sputteringmentioning
confidence: 99%
“…59,60 In vitro studies have shown that these coatings exhibit enhanced bioactivity and biomineralisation over uncoated samples and pure HA coatings. [61][62][63] Fig. 3 shows a typical example of osteoblast response to a magnetron co-sputtered Si-HA thin film.…”
Section: Magnetron Sputteringmentioning
confidence: 99%
“…Silicate-substituted HA, Ca 10 (PO 4 ) 6Àx (SiO 4 ) x (OH) 2Àx , has received a great deal of interest recently as a potential bone substitute material [9,89]. The silicatecontaining HA-based (Si-HA) coatings have shown an improvement in biological performance over their undoped counterparts [90,91]. Cells were either kept in proliferation medium (a, c) or in osteogenic medium (b, d) [87] As a measure to achieve the dual aims of bacterial inhibition and enhancement of osteoblast functions of implant materials, silver-containing HA (Ag-HA) composite coatings are of special interest.…”
Section: Antimicrobial and Bioactive Coatingsmentioning
confidence: 99%
“…Silver or silicate could be incorporated into HA prior to the deposition process, or Ag (or Si) and HA could be utilized as two separate coating targets. Based on the success of Si-substituted apatite bone grafts, the coatings prepared via RF magnetron co-sputtering of HA and Si targets were investigated by Thian et al [90,91,98].…”
Section: Antimicrobial and Bioactive Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, rough and porous surfaces could stimulate cell attachment and formation of extra-cellular matrix [73]. The biological benefits/effects of biomimetic HA [63,[74][75][76] and the possibilities to use them as coatings on titanium implants for improving the biological responses have been reported. However, only a few of the developed ion-substituted and/or ion doped hydroxyapatite coatings have been tested in vitro and/or in vivo, and the improvement of the biological response due to ion substitution is thus still just a hypothesis [20,27,[77][78][79].…”
Section: Biological Response Of Biomimetic Ha Coatingsmentioning
confidence: 99%